Romania’s National Plan against Illegal Logging: An Analysis of the Public Proposal - Cristian Bălăcescu, Marian (Journal of Development Policy Research and Practice (JoDPRP), 2020)
This study analyses the extent to which the Romanian National Plan Against Illegal Logging (Planul Național de Combatere a Tăierilor Ilegale de Arbori (PNCTIA) fulfils the conditions of a functional public policy proposal; the degree of knowledge specialists (forestry staff, policemen, prosecutors); and the general public have about it; what efficiency they attribute to it; and the need for a new strategy. The main limitations of PNCTIA with respect to defining and formulating the public policy issue were identified using the document analysis technique. Moreover, the questionnaire technique was employed to evaluate the specialists and the public view towards the plan. Over 40% of the interviewees consider PNCTIA to be inefficient, while 33% were undecided. 77% wished for the adoption of a new public policy; 85% highlighted the matter as urgent. The low level of efficiency of PNCTIA was correlated with the need to have another intervention plan and with high urgency to implement the measures. The perspective of having a new programme correlates positively both with institutional involvement and with urgency level of the actions. The study highlights the importance of participatory processes in the development of public policies. The scope of this article is related to the following SDG / SDGs.